ANALISIS PEMASARAN TANDAN BUAH SEGAR KELAPA SAWIT PETANI SWADYA DI DESA PAYUNG KABUPATEN BANGKA SELATAN (Marketing Analysis Of Fresh Fruit Bunches Of Oil Palm By Independent Farmers In Payung Village, South Bangka Regency) - PUTRI, JUHANA; SITORUS, ROSTIAR; PURWASIH, RATI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2026)
The focus of this study is to (1) identify the marketing channels for fresh fruit bunches (FFB) of oil palm produced by smallholder farmers, (2) describe the marketing functions performed by each marketing institution, and (3) analyze the efficiency of the marketing channels used in Payung Village, South Bangka Regency. Using a descriptive quantitative approach conducted from mid-June to July 2025, this study mapped the marketing flow, the roles of relevant institutions, and their efficiency levels. Snowball sampling revealed that smallholder farmers, collector traders, and palm oil mills form the dominant marketing chain. The analysis results indicate that traders largely assume logistical roles and risk management, while farmers participate in storage functions. Specifically, first-tier collector traders were identified as the most efficient channel, with the lowest margin of Rp120–Rp150/kg and a farmer’s share reaching 95.74%.